Outcomes of Sacral Nerve Stimulation for Treatment of Refractory Overactive Bladder Among Octogenarians. Issue 6 (19th June 2019) - Greenberg, Daniel R.; Syan, Raveen; Young‐Lin, Nichole; Comiter, Craig V.; Enemchukwu, Ekene
Abstract : Objective: Sacral nerve stimulation (SNS) is an effective treatment for refractory overactive bladder (OAB). However, advanced age is often cited as a reason to avoid SNS in the elderly. This study evaluates the safety and efficacy of SNS for refractory OAB among our octogenarian population. Methods: A retrospective review from a single institution was performed on all SNS lead placements from December 1998 to June 2017 for refractory OAB. Octogenarians were characterized as 80 years of age or older at the time of Stage I. Efficacy and safety were determined by the rate of progression to Stage II, subsequent need for multimodal therapy, and rate of surgical revision and explantation. All patients were followed for a minimum of 12 months. Results: Of 374 patients in this study, 37 (9.9%) were octogenarians. There was no difference in gender, race, smoking history, or prior OAB treatment regimens between cohorts. The rate of progression to Stage II was 56.8% for octogenarians compared to 60.5% for nonoctogenarians ( p = 0.66). The rate of surgical revision, explantation, and need for multimodal therapy did not differ between groups. Subgroup analysis of octogenarians did not reveal any significant differences between successful and nonsuccessful Stage I patients. Conclusions: The safety and efficacy of SNS was similar between cohorts. This result suggests that SNS is a safe and effective therapy that should be considered among the treatment options for refractory OAB in octogenarian patients. Further studies are needed to determine predictive factors of Stage I success in elderly patients.